Thyroid dysfunction in MASLD: Results of a nationwide study - Shuai Yuan; Fahim Ebrahimi; David Bergman; Marijana Vujković; Eleonora Scorletti; Xixin Ruan; Jie Chen; Hannes Hagström; Jonas F. Ludvigsson (JHEP Reports)
Background & Aims: Thyroid hormones are known to be potent modulators of hepatic metabolism and targeting the thyroid hormone receptor was recently approved as the first treatment for metabolic-associated steatotic liver disease (MASLD); however, the exact relationship between thyroid disorders and biopsy-confirmed MASLD remains unclear. Methods: We conducted a nationwide matched case–control study leveraging data from the Swedish Epidemiology Strengthened by histoPathology Reports in Sweden (ESPRESSO) cohort, which includes liver biopsy data spanning from 1969 to 2017. We identified 12,172 patients with MASLD and 56,831 matched general-population controls, including 5,478 patients with MASLD with 10,682 sibling controls. Conditional logistic regression was used to calculate odds ratios for hypothyroidism and hyperthyroidism defined through ICD codes or prescription records. Causal inference was examined using Mendelian randomization (MR). Both observational and MR mediation analyses were performed to explore the roles of metabolic features. Results: Hypothyroidism was associated with 1.68-fold increased odds of MASLD (95% CI 1.36–2.06). The association remained stable in the analysis using siblings as controls. However, in absolute terms, hypothyroidism was uncommon and seen in 2.5% in people with MASLD and in 1.4% of controls. Higher genetically predicted thyroid-stimulating hormone levels and hypothyroidism were linked to increased MASLD risk. Mediation analysis showed that metabolic disorders contributed ∼41% to this risk. Furthermore, there was an inverse association between hyperthyroidism and MASLD (adjusted odds ratio 0.17, 95% CI 0.05–0.56); however, the association did not reach statistical significance in the MR analysis. Conclusions: The findings suggest that hypothyroidism is associated with a heightened risk of MASLD and that hyperthyroidism is potentially protective against MASLD. Impact and implications: The approval by the US FDA of resmetirom, a thyroid hormone receptor β-selective agonist for non-cirrhotic metabolic dysfunction-associated steatohepatitis with stage 2–3 fibrosis, highlights the potential role of thyroid dysfunction in metabolic-associated steatotic liver disease (MASLD). This study identified hypothyroidism as a risk factor for MASLD, especially in men and individuals younger than 40 years, with the association peaking at non-cirrhotic fibrosis. Metabolic disorders mediated ∼41% of the hypothyroidism–MASLD association. Hyperthyroidism was potentially inversely associated with MASLD. Despite its low prevalence (2.5% in MASLD cases, 1.4% in controls), the population health impact of hypothyroidism warrants further attention.